Engineering management in developing countries a future prospective - Eusuf, Muhammad Abu; Mohd. Din, Shamzani Affendy; Mohamed Ali, Haitham; Khaleed Mansour, Abeer (International Journal of Technical Research and Applications, 2015)
As a result of globalization, one of the most major issues affecting the success of projects would be the formation of a multicultural project management style. As projects leaders continue to lead global, multicultural projects, there is a demand for managing a workforce that is more diverse than ever. The multi-generational workforce has distinct views on work ethic, communication and incentives; finding common ground is essential. As the world of multinational projects is rapidly developing new concepts and methodologies are being introduced, especially in the management direction, as well as, the serious need for the use of engineering management modern practices. In many developing countries now the mega projects are multicultural projects different designers, contractors, subcontractors and suppliers from all over the world work together to achieve excellence but such projects bring with it many challenges on how all these people from different background, different laws, policies, legislations and ways of work can achieve harmony and finalize the projects within vale and time. Here comes the serious need for engineering and managers to design and provide a system that allows the projects such as construction process to be organized, harmonized and achieve the best quality from such activities and projects at the same time minimizing various risks to the minimum. The increase of the citizens of the globe and its urban population calls for more construction activities especially for accommodation .in developing countries, in general ,the rate of construction is far below the demand for shelter , infrastructure and other amenities .many factors such as demographic growth, shifts from rural to urban areas, natural and human made resources depletion, and significant changes in expectations and life styles, all combine in their various ways impose considerable pressure on the construction industry of developing countries. From this prospect comes the urgent need to engineering management to be introduced in these developing countries and for its recommendations and reflections to become a practical actions specially its effects of laws and new policies to ensure ease of operations and motivation of investors both externally and internally.